Adaptation of a hospital electronic referral system for antimicrobial stewardship prospective audit and feedback rounds. (4th May 2018) - Rawlins, Matthew D M; Raby, Edward; Sanfilippo, Frank M; Douglass, Rae; Chambers, Jonathan; McLellan, Duncan; Dyer, John R
Abstract: Objective: To evaluate the impact of the adaptation of an existing electronic referral application for use in antimicrobial stewardship prospective audit and feedback rounds (antimicrobial rounds). Design: Retrospective, single-centre observational study between March 2015 and February 2016. Setting: A new quaternary referral centre. Study Participants: Adults referred for antimicrobial rounds outside of the intensive care and haematology units. Intervention: Adaptation of an electronic referral application used by medical and allied health staff. A questionnaire-style referral form was designed to capture patient clinical details using a combination of free text and dropdown menus. Clinical pharmacists were educated and granted access to the system. Main Outcome Measures: The proportion of completed electronic referrals of total round reviews by month for the 12 months after implementation. The time from request to completion of reviews. The impact on adherence to advice provided on rounds. The impact on the institutional usage of broad-spectrum antibiotics: glycopeptides, carbapenems, third and fourth generation cephalosporins, fluoroquinolones and piperacillin/tazobactam. Results: Over the study period, the proportion of electronic referrals of completed antimicrobial round reviews increased from 59% to 88% ( P < 0.001); 75.7% of accepted electronic referrals were seen within 48 h of request. The proportion of advice ignored fell from 18% to 8.5% ( P < 0.001). Piperacillin/tazobactam, fluoroquinolone and glycopeptide usage decreased. Conclusions: The adaptation of an electronic referral application for antimicrobial rounds was associated with increased adherence to advice and reduction in use in target antibiotics. Our model is now used at other institutions.